2012
DOI: 10.1111/tpj.12038
|View full text |Cite
|
Sign up to set email alerts
|

ZmGA3ox2, a candidate gene for a major QTL,qPH3.1, for plant height in maize

Abstract: SUMMARYMaize plant height is closely associated with biomass, lodging resistance and grain yield. Determining the genetic basis of plant height by characterizing and cloning plant height genes will guide the genetic improvement of crops. In this study, a quantitative trait locus (QTL) for plant height, qPH3.1, was identified on chromosome 3 using populations derived from a cross between Zong3 and its chromosome segment substitution line, SL15. The plant height of the two lines was obviously different, and appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 63 publications
(66 reference statements)
4
95
0
2
Order By: Relevance
“…The mutation in d1-6016 allele was also independently found in GA3ox2 recently. 9 Thus, these results confirmed that ZmGA3ox2 is the causative gene for d1 phenotype. Enzymatic analysis of D1 protein indicated that it can catalyze at least 4 reactions leading to bioactive GA formation: GA 9 to GA 4 , GA 20 to GA 1 , GA 20 to GA 3 , and GA 5 to GA 3 .…”
Section: Introductionsupporting
confidence: 78%
“…The mutation in d1-6016 allele was also independently found in GA3ox2 recently. 9 Thus, these results confirmed that ZmGA3ox2 is the causative gene for d1 phenotype. Enzymatic analysis of D1 protein indicated that it can catalyze at least 4 reactions leading to bioactive GA formation: GA 9 to GA 4 , GA 20 to GA 1 , GA 20 to GA 3 , and GA 5 to GA 3 .…”
Section: Introductionsupporting
confidence: 78%
“…This extends the previous analysis that the d1 mutation blocked three steps in GA biosynthesis (Spray et al, 1996). Together with the report that ZmGA3ox2 is a candidate gene for a major quantitative trait locus for plant height (qPH3.1; Teng et al, 2013), these results indicate that D1 encodes ZmGA3ox2, a GA3ox that catalyzes the final step of GA biosynthesis.…”
Section: D1 Encodes a Ga3ox Catalyzing The Final Step Of Ga Biosynthesupporting
confidence: 70%
“…7), suggesting that ZmGA3ox1 plays a minor role in GA biosynthesis in major tissues. It was reported that ZmGA3ox1 was expressed in the immature tassel (Teng et al, 2013). Thus, it is possible that ZmGA3ox1 is expressed at a very low level or in limited cell types, such as in a few cells in immature tassels.…”
Section: D1 Encodes a Ga3ox Catalyzing The Final Step Of Ga Biosynthementioning
confidence: 99%
“…D8 is a negative GA-responsive regulator in maize [86] , and its orthologs in Arabidopsis (GAI) [87] and wheat (Rht) [88] share a conserved DELLA domain that is important for the recognition of GAs. ZmGA3ox2 (D18), an ortholog of OsGA3ox2, encoding a GA3β-hydroxylase, has a similar expression pattern to OsGA3ox2, which has been confirmed as controlling the elongation of the vegetative shoot [89] . Here we showed that mRNAs corresponding to four probe sets (Zm.13480.1.S1_at and Zm.390.1.S1_at) were significantly changed in the maize internode elongation responses to ethephon treatment.…”
Section: Possible Roles Of Plant Hormone Pathway and Expression In Inmentioning
confidence: 90%